Lymphatic-derived oxysterols promote anti-tumor immunity and response to immunotherapy in melanoma - Mengzhu Sun; Laure Garnier; Romane Chevalier; Martin Roumain; Chen Wang; Julien Angelillo; Julien Montorfani; Robert Pick; Dale Brighouse; Nadine Fournier; David Tarussio; Stéphanie Tissot; et al. (Nature Communications)
Abstract In melanoma, lymphangiogenesis correlates with metastasis and poor prognosis and promotes immunosuppression. However, it also potentiates immunotherapy by supporting immune cell trafficking. We show in a lymphangiogenic murine melanoma that lymphatic endothelial cells (LECs) upregulate the enzyme Ch25h, which catalyzes the formation of 25-hydroxycholesterol (25-HC) from cholesterol and plays important roles in lipid metabolism, gene regulation, and immune activation. We identify a role for LECs as a source of extracellular 25-HC in tumors inhibiting PPAR-γ in intra-tumoral macrophages and monocytes, preventing their immunosuppressive function and instead promoting their conversion into proinflammatory myeloid cells that support effector T cell functions. In human melanoma, LECs also upregulate Ch25h, and its expression correlates with the lymphatic vessel signature, infiltration of pro-inflammatory macrophages, better patient survival, and better response to immunotherapy. We identify here in mechanistic detail an important LEC function that supports anti-tumor immunity, which can be therapeutically exploited in combination with immunotherapy.